HUBUNGAN HIGIENE PERORANGAN DAN SANITASI MAKANAN RUMAH TANGGA DENGAN KEJADIAN DEMAM TIFOID PADA ANAK UMUR 5-14 TAHUN DI WILAYAH KERJA PUSKESMAS BANDARHARJO KOTA SEMARANG - Malau, Vinta Mariko; Budiyono, Budiyono; Hanani D., Yusniar (Jurnal Kesehatan Masyarakat (Undip), 2015)
Typhoid fever is a disease caused by Salmonella typhii and it spreads in fecal-oral way through food and drink. The number of typhoid and paratyphoid fever sufferer in Semarang Bandarharjo Health Centre has increased, from 2011 to 2012 it reached 10.8% and from 2012-2013 up to 23.5%. Most cases on children 5-14 years old. The purpose of this study was to analyse the relation between a child hygiene, food handlers hygiene and household food sanitation with the incidence of typhoid fever on children 5-14 years old in Semarang Bandarharjo Health Centre working area. This study applied observational analytic research with case control design. The population was all children aged 5-14 years old suffering and not suffering from typhoid fever. The sample taken was as many as 43 cases and 43 controls.  The data was analysed using chi-square test with standard error (α) 5%. The result of this study shows that there is relation between hand washing habit before eating in children (p-value=0,042), hand washing habit after defecation in children (p-value=0,002), hand washing habit of food handlers before handling the food (p-value=0,045), hand washing habit of food handlers after defecation (p-value=0,002), the cooking process of food by food handlers before consumed (p-value=0,017) with the incidence of typhoid fever and there is no relation  between the practice of washing the food ingredients by food handlers (p-value=0,126), the practice of cleaning of eating utensils by food handlers (p-value=0,113), the boiling of water before consumed  (p-value=0,017) with the incidence of typhoid fever. In conclusion, personal hygiene and food sanitation are risk factors to the incidence of typhoid fever on 5-14 years old in Semarang Bandarharjo Health Centre working area.